Estrategias metodológicas para mejorar el nivel de aprendizaje de los niños y niñas del primer año de Educación Básica del Liceo Prof. Angel Baldomero Nagua del Cantón Pasaje, año lectivo 2010-2011. - Villacrés Prieto, Priscila Marcela (2011)
The present investigation was carried out with the purpose of determining the factors that affect the inadequate application of methodological strategies in the teaching-learning process of the children of the first year of Basic Education of the Liceo Prof. Ángel Baldomero Nagua del Canton Pasaje, academic year 2010-2011.